Test-driven development, refactoring and pair programming - Beecham, Bryan (LiveLessons., 2014)
"Offering more than 4 hours of instruction, this fast-paced and engaging video course recorded as a live workshop teaches the essentials of test-driven development, refactoring, and pair programming."--Resource description page.